HiPS-Endothelial Cells Acquire Cardiac Endothelial Phenotype in Co-culture With hiPS-Cardiomyocytes - Helle, Emmi; Ampuja, Minna; Dainis, Alexandra; Antola, Laura; Temmes, Elina; Tolvanen, Erik; Mervaala, Eero; Kivelä, Riikka (Frontiers in Cell and Developmental Biology, 2021)
Cell-cell interactions are crucial for organ development and function. In the heart, endothelial cells engage in bidirectional communication with cardiomyocytes regulating cardiac development and growth. We aimed to elucidate the organotypic development of cardiac endothelial cells and cardiomyocyte and endothelial cell crosstalk using human induced pluripotent stem cells (hiPSC). Single-cell RNA sequencing was performed with hiPSC-derived cardiomyocytes (hiPS-CMs) and endothelial cells (hiPS-ECs) in mono- and coculture. The presence of hiPS-CMs lead to increased expression of transcripts related to vascular development and maturation, cardiac development, as well as cardiac endothelial cell and endocardium -specific genes in hiPS-ECs. Interestingly, coculture induced the expression of cardiomyocyte myofibrillar genes and MYL7 and MYL4 protein expression was detected in hiPS-ECs. Major regulators of BMP- and Notch-signaling pathways were induced in both cell types in coculture. These results reflect the findings from animal studies and extend them to human endothelial cells, demonstrating the importance of EC-CM interactions during development.